The Road to the Salvation of Mankind: Additions to the Series of Glass Designs by the Crabeth Brothers - van Ruyven-Zeman, Zsuzsanna (The Rijksmuseum Bulletin, 2021)
The two newly-discovered drawings by the glass painter Dirck Crabeth presented here fit seamlessly into his series The Road to the Salvation of Man, which has long been known. The drawings are the design for the first episode, until recently known only as a glass panel, and the original of the second episode, the copy of which, along with two copies of other episodes are in Museum Catharijneconvent in Utrecht. Stylistic clues have made it possible to date Dirck Crabeth’s drawings and the corresponding surviving glass panels earlier, to around 1545-50. They share the thinking represented in a Lutheran series of prints by Frans Huys dating from around 1560 to a design by Gerard van Groeningen, which was discussed by Daniel Horst. An analysis of the career of the young Wouter Crabeth, his collaboration with Dirck and characteristics of their different styles demonstrates that the three copies in Utrecht could be by Wouter Crabeth, contrary to the recent attribution by Ilja Veldman to the Antwerp artist Pieter Huys, Frans’s brother, and in line with the previously held attribution to one of Dirck’s assistants.